The Political Economy of Risk in Finance and the Military - Schelhase, Marc. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This book offers a compelling argument, a warning as well as hope for the very challenges of living with and through risk." - Mikkel Vedby Rasmussen, Professor and Dean, Faculty of Social Sciences, University of Copenhagen, Denmark "Marc Schelhase provides a fascinating account on how risk is constituted and lived by different actors in different contexts." - Andreas Nölke, Professor, Institute of Political Science, Goethe University Frankfurt/Main, Germany "Closely argued, thoroughly convincing and something of a guidebook for the world in which we now find ourselves, this is highly recommended." -Colin Hay, Professor, Sciences Po, Paris, France This book is about risk conceptions, experiences and reflections. It applies the concept of the risk triangle, with its societal, organisational and personal angles, to two areas of inquiry: financial markets and the military, seeking to demonstrate the challenges, dilemmas and, in many ways, also the impossibilities of risk analysis and risk management. Drawing on empirical and micro- and macro-level analysis, this innovative work will appeal to students of political science, economics and business as well as to risk professionals and risk-takers. Marc Schelhase is Senior Lecturer in the Defence Studies Department, School of Security Studies, King's College London at the Joint Services Command and Staff College, UK Defence Academy.
1. Varieties of risk -- 2. Bringing the harm home - applying the concept of social harm to home ownership -- 3. 'Reason is just one letter away from treason' - exploring risk in defence procurement -- 4. Realities of conflict - risk and military decision-makers -- 5. Exploring organisational risk dynamics - insights and challenges to organisational risk management -- 6. Risking money, risking lives - thinking critically about risk, thinking beyond risk.
Keywords: International relations; Politics and war; Risk management; International Relations; Military and Defence Studies; IT Risk Management